FACTORS AFFECTING THE PERCEPTION OF TAX EVASION AND ITS IMPACTS ON THE PERCEPTION OF TAX COMPLIANCE (Case Study on Accounting Students in West Java) - Rindianti Rindianti; Indah Umiyati; Bambang Sugiharto (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
This study aims to determine the effect of Philosophy of Ethics, Religiosity, Understanding of Taxation, and Love of Money on Perceptions of Tax Evasion and Their Impact on Tax Compliance among students majoring in accounting in West Java. This study uses primary data, namely a questionnaire in the form of a Google form. This research has a population of students majoring in accounting in West Java and the sample is non-probability sampling with purposive sampling technique. As well as in this study using a quantitative approach, data analysis used by path analysis. The results showed that partially (t test) the Ethical Philosophy (Relativism), Religiosity, and Understanding of Taxation variables had no effect on Perceptions of Tax Evasion. Perceptions of tax evasion have no effect on perceptions of tax compliance. However, the Ethical Philosophy (Idealism) and Love of Money variables influence the perception of tax evasion. The simultaneous results (f test) show that ethical philosophy, religiosity, understanding of taxation, love of money have an indirect effect on perceptions of tax compliance through perceptions of tax evasion.